OPTIMIZATION WITH JACOBIAN APPROACH FOR DIVING MOTION OF ROV SYSTEM - Teguh Herlambang (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Indonesia is a country with a large watery area of about two thirds of the country's total territory. Therefore, the country requires a multifunctional vehicle that can be utilized for a mitigation in river and a maritime defense system. One of the multifunctional vehicles is the Remote Operated Vehicle (ROV). In this paper the optimization of ROV system with Jacobian approach for ROV system is studied. With jacobian approach, linearization of nonlinear ROV system to analyze controllabity and observability without control system could be accomplished. Linear system for diving motion of ROV has a 3 DOF model, which are surge, heave, and pitch. Results of the optimization with Jacobian approach show that the ROV system is controllable and observable. Keywords: AUV, optimization, Jacobian, linear system, controllable, observable